Atividade inseticida e repelente do óleo essencial de Pelargonium graveolens em Musca domestica e Lucilia cuprina - Saraiva, Luana Carvalho (2018)
The use of essential oils with insecticidal activity has been widely studied, providing a new treatment alternative, since conventional synthetic insecticides, due to their toxic potential and indiscriminate use have caused an increase of resistant species, causing significant damages to human and animals health.In this context, the use of essential oils can contribute significantly to the control of insects.The objective of this work was to investigate the insecticidal activity of the essential oil of Pelargonium graveolens against two species of flies.For this, larvicidal tests were performed, using four concentrations of oil (2.5%, 5%, 10% and 20%), a negative control with Tween-80 and a positive control containing Diazinon.The adulticidal tests were performed using impregnated paper and topical application techniques, both with concentrations of 1%, 2.5%, 5% and 10%, acetone and Diazinon as negative and positive controls, respectively.The repellency test was also performed with the difference of 1% of the essential movement, 1% Tween-80 as a positive control and 1% Diazinon as positive control.All tests were performed in triplicate. The essential oil of P. graveolens did not present larvicidal potential on the two species of insects.In the adulticidal test of the impregnated paper, a 100% mortality at 120 minutes was observed in M. domestica and in L. cuprina the 1% concentration was effective at 60 minutes, killing 100% of the flies.In 120 minutes of superficial application test the essential oil in the 5% concentration presented 100% mortality for M. domestica and for L. cuprina, the essential oil 5% and 10% presented mortalities of 96% and 100% in 45 minutes, respectively.The essential oil of P. graveolens (1%) presented a repellent effect.Thus, P. graveolens oil can be used as a form of natural control of M. domestica and L. cuprina, reducing the use of chemical insecticides commonly used to control these dipterous.